Long-segmental tracheal reconstruction in rabbits with pedicled Tissue-engineered trachea based on a 3D-printed scaffold. (1st October 2019) - Gao, Botao; Jing, Hui; Gao, Manchen; Wang, Shoubao; Fu, Wei; Zhang, Xiaoyang; He, Xiaomin; Zheng, Jinghao
Graphical abstract: Abstract: Long-segmental tracheal defects constitute an intractable clinical problem, due to the lack of satisfactory tracheal substitutes for surgical reconstruction. Tissue engineered artificial substitutes could represent a promising approach to tackle this challenge. In our current study, tissue-engineered trachea, based on a 3D-printed poly (l -lactic acid) (PLLA) scaffold with similar morphology to the native trachea of rabbits, was used for segmental tracheal reconstruction. The 3D-printed scaffolds were seeded with chondrocytes obtained from autologous auricula, dynamically pre-cultured in vitro for 2 weeks, and pre-vascularized in vivo for another 2 weeks to generate an integrated segmental trachea organoid unit. Then, segmental tracheal defects in rabbits were restored by transplanting the engineered tracheal substitute with pedicled muscular flaps. We found that the combination of in vitro pre-culture and in vivo pre-vascularization successfully generated a segmental tracheal substitute with bionic structure and mechanical properties similar to the native trachea of rabbits. Moreover, the stable blood supply provided by the pedicled muscular flaps facilitated the survival of chondrocytes and accelerated epithelialization, thereby improving the survival rate. The segmental trachea substitute engineered by a 3D-printed scaffold, in vitro pre-culture, and in vivo pre-vascularization enhanced survival in an early stage post-operation, presenting a promising approach for surgical reconstruction of long segmental tracheal defects. Statement of Significance: We found that the combination of in vitro pre-culture and in vivo pre-vascularization successfully generated a segmental tracheal substitute with bionic structure and mechanical properties similar to the native trachea of rabbits. Moreover, the stable blood supply provided by the pedicled muscular flaps facilitated the survival of chondrocytes and accelerated epithelialization, thereby improving the survival rate of the rabbits. The segmental trachea substitute engineered by a 3D-printed scaffold, in vitro pre-culture, and in vivo pre-vascularization enhanced survival in an early stage post-operation, presenting a promising approach for surgical reconstruction of long segmental tracheal defects.